Integrating Service-Learning Pedagogy: A Faculty Reflective Process - Carmen Carracelas-Juncal, PhD; Jenny Bossaller, PhD; Gallayanee Yaoyuneyong, PhD (Park University, 2009)
Research on service-learning has focused mainly on student outcomes. However, this study addresses the transformative change that three faculty members from different disciplines experienced during a semester-long fellowship on service-learning as a pedagogical method. Through their personal reflections, the authors show how service-learning and the scholarship of teaching were intertwined as they engaged in course redesign. This experience went beyond creating an academic service-learning course to transforming the teachers into reflective practitioners actively engaged in systematically improving their teaching practice.